Life Cycle Assessment of an Innovative Food Waste Management System - Elginoz, Nilay; Khatami, Kasra; Owusu-Agyeman, Isaac; Cetecioglu, Zeynep (Frontiers in Sustainable Food Systems, 2020)
The aim of this study has been to investigate the environmental impacts of an innovative food waste management system and compare it with landfilling as a conventional waste management option. The investigated system is still in the laboratory research and development phase. Therefore inventory data of the laboratory scale food waste management system was collected and then up-scaled for life cycle assessment purposes. The proposed system consists of a hygenization reactor followed by a fermenter and then a centrifuge. The system converts food waste into volatile fatty acid-rich supernatant. Functional unit is management of 1 ton food waste. The results indicate that the proposed system is a better option than landfilling in terms of all impact categories. The produced VFA-rich supernatant is supposed to be used as a replacement for methanol in the denitrification process. In one of the impact categories (ozone depletion potential) the avoided burdens are higher than the burdens and the system provides net gain (-2.82E-07 kg R11 eq.). Majority of the environmental burdens in the proposed system are due to heat consumption for hygenization. Including sludge disposal in the investigated system boundary increases the environmental burdens but the burdens are still lower compared to landfilling option.